Eco Grocer Online Ordering System with Data Retention Policy - Mohd Yusri, Atieleya Batrisha; Ab Rahman, Nurul Hidayah (Applied Information Technology And Computer Science, 2024)
Eco Grocer is a grocer shop that sells daily necessities such as groceries. Currently, Eco Grocer only depends on customers that are shopping physically, and the business is not well-known in the area. By adopting the online ordering system, it helps to widen the market. Eco Grocer online ordering system is an ordering system developed to ease customers to buy necessities. However, it is very risky to provide personal information on online ordering system since there are a lot of data breaches happen not only towards small business, but large organizations are not exceptional. Thus, implementing data retention policy is the best practice to reduce the risk of old unuse data being stolen or exploited by attackers Therefore, this study proposed Eco Grocer Online Ordering System with data retention policy to facilitate secure data management. This system is developed using Object-Oriented Programming with PHP programming language. The system is successfully developed to incorporates four modules that are Sign Up/Log In, Product List, User Profile and Checkout Page. By applying data retention policy on User Profile module, it could reduce the risk of data breach attack to protect the confidentiality of the customers’ personal information stored in the database by storing all the customers’ data in a certain period before it will be deleted or archived to the tertiary storage. This system has undergone several testing, including system functionality testing, system design testing and data retention testing. All of the testing conducted was successful. It indicates that the system is in a good state in terms of functionality, design and security.